Homicide Or Accident? Meticulous Forensic Investigation Solved The Case - A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
History plays a great role in crime investigation. Inspite of that, autopsy findings and circumstantial evidence can lead to the actual truth. A 16-year-old boy was brought to the emergency with profuse bleeding from his left axilla and was declared dead. It was an alleged case of homicide, complained by the family members of the decease but after thorough investigation and post-mortem findings, the case led to somewhere else. It was claimed that victim was killed by his friends during a birthday party celebration. Autopsy finding revealed an incised wound over left axilla which led to transection of axillary artery and the victim died due to hypovolemic shock. Circumstantial evidence corroborated with autopsy findings and finally manner of death was established as accident.
Keywords: Autopsy, Axillary Artery, Homicide, Suicide.